Answer:
$3.57
Step-by-step explanation:
You multiply .40 by 2.55 which gives you 1.07 then you add that to the original
Answer:
3.57 dollars
Step-by-step explanation:
Cost of sandwich = $2.55
We are given that To make a profit, the deli sells it at a price that is 140% of the cost
So, selling price of sandwich = [tex]140\% \times 2.55[/tex]
= [tex]\frac{140}{100} \times 2.55[/tex]
= [tex]3.57[/tex]
Hence The sandwich sells for 3.57 dollars
a taxi charges $1.75 for the first 1/8 mile and $0.30 for each additional 1/8 mile write an equation that gives the cost c of a taxi ride in terms of the number of miles m how many miles did you drive if a ride cost $7.75
The cost of a taxi ride can be calculated using the equation c = 1.75 + (m - 1/8) * 8 * 0.30, where c represents the total cost and m represents the total miles driven. Solving this equation for m when the total cost is $7.75 would yield the number of miles driven.
Explanation:The subject of this question is the creation of an equation to calculate the cost of a taxi ride. According to the question, a taxi charges $1.75 for the first 1/8 mile and $0.30 for each additional 1/8 mile. First, we need to convert miles to 1/8 miles, since the pricing is based on this fraction. We know that each full mile is equal to 8 fractions of 1/8 mile. Therefore, to convert miles to 1/8 miles, we multiply the number of miles by 8.
Given this pricing structure, the costs associated with additional miles driven beyond the first 1/8 mile (which are already accounted for by the initial $1.75), can be represented by (m-1/8)*8*0.30. Here, (m-1/8) represents the additional miles traveled beyond the first 1/8 mile, and multiplying this by 8 converts these miles into 1/8 miles.
The total cost, c, can thus be represented by the equation c = 1.75 + (m - 1/8) * 8 * 0.30. If a ride cost $7.75, we can substitute this cost into the equation and solve for m to find the number of miles driven. This would give us the equation: 7.75 = 1.75 + (m - 1/8) * 8 * 0.30.
Learn more about Algebra here:https://brainly.com/question/32436021
#SPJ2
I need help please ?!!!
Answer: B
Step-by-step explanation:
-19 + (-23)
Answer:
-19-23 is basically 19+23 but in the negatives.
so B is your answer
Step-by-step explanation:
The sun produces 3.9 * 10^33 ergs of radiant energy per second. How many ergs of radiant energy does the sun produce in 3.25 * 10^3 seconds?
Answer: [tex]1.2675*10^{37}\ ergs[/tex]
Step-by-step explanation:
Let be "x" the amount of ergs the sun produces in[tex]3.25 * 10^3\ seconds[/tex].
According to the information provided in the exercise, in 1 second the sun produces [tex]3.9 * 10^{33}\ ergs[/tex] of radiant energy.
Then, in order to find the value of "x" you can write the following proportion:
[tex]\frac{ 3.9 * 10^{33}\ ergs}{1\ second}=\frac{x}{3.25 * 10^3\ seconds}[/tex]
Finally, you must solve for "x".
Therefore, you get:
[tex]x=\frac{( 3.9 * 10^{33}\ ergs)( 3.25 * 10^3 seconds)}{1\ second}\\\\x=1.2675*10^{37}\ ergs[/tex]
Six times the product of negative five and a number
please show steps
Answer:
Step-by-step explanation:
Steps:
1. Let x = #
2. "Five less than six times a number" can be written as: 6x - 5
3. "is at least" is the same as "greater than or equal to" and can be written as: >=
4. "nine subtracted from two times that number" can be written as: 2x - 9
5. the equation is: 6x - 5 >= 2x - 9
6. solve for x by grouping the x variable terms on one side and the constants on the other side:
6x - 5 >= 2x - 9
-2x +5 -2X +5
4x >= -4
7. divide each side by 4, and you get: x = -1
The solution according to the given statement is "x = -1".
According to the question,
The equation will be:
[tex]6x - 5 \geq 2x - 9[/tex]By adding "5" both sides, we get
→ [tex]6x - 5+5 \geq 2x - 9+5[/tex]
→ [tex]6x \geq 2x-4[/tex]
By subtracting "2x" form both sides, we get
→ [tex]6x-2x \geq 2x-4-2x[/tex]
→ [tex]4x \geq -4[/tex]
→ [tex]x \geq -\frac{4}{4}[/tex]
→ [tex]x = -1[/tex]
Thus the above answer is appropriate.
Learn more:
https://brainly.com/question/13536824
14:2
= 20: wat is the equivalent ratio
Answer:
[tex]\large\boxed{14:2=20:\dfrac{20}{7}}[/tex]
Step-by-step explanation:
[tex]14:2=20:x\\\\\dfrac{14\!\!\!\!\!\diagup^7}{2\!\!\!\!\diagup_1}=\dfrac{20}{x}\\\\\dfrac{7}{1}=\dfrac{20}{x}\qquad\text{cross multiply}\\\\7x=(20)(1)\\\\7x=20\qquad\text{divide both sides by 7}\\\\x=\dfrac{20}{7}[/tex]
A car manufacturer estimates that 25% of the new cars sold in one city have defective engine
mounts.
If 2,688 new cars are sold in that city, about how many will have defective engine mounts?
Answer: 672 cars will have defective engine mounds
Step-by-step explanation: 25% of 2,688 is 672
Identify the equivalent of:
6x + 2y = 12
A. y = 3x + 6
B. y = -3x - 6
C. y = 3x - 6
D. y = -3x + 6
Answer:
D. y = -3x + 6.
Step-by-step explanation:
6x + 2y = 12
2y = -6x + 12 Divide through by 2:
y = -3x + 6.
Answer:
D. y = -3x + 6
Step-by-step explanation:
6x + 2y = 12
-6x - 6x
_____________
2y = -6x + 12
__ ________
2 2
[tex]y = -3x + 6[/tex]
I am joyous to assist you anytime.
A set of data has a mean of 45.6 what is the mean if 5.0 is added to each score
Answer:
The mean will be increased by 5
Step-by-step explanation:
Suppose a set of data [tex](2, 4, 6, 8, 10, 12)[/tex]
Mean is defined as sum of all the values given set of data divided by total number of values.
Mean1 = [tex]\frac{2+4+6+8+10+12}{6} = \frac{42}{6} = 7[/tex]
Now if we add 5 toeach value, the new set becomes [tex](7, 9, 11, 13, 15, 17)[/tex]
for which,
Mean2 = [tex]\frac{7+9+11+13+15+17}{6} = \frac{72}{6} = 12[/tex]
Mean2 - Mean1 = 5
Peppers are priced 3 for $1.02 . How much would one pepper cost
Answer:
0.34 cents
Step-by-step explanation:
You simply divide 1.02 by the 3 peppers.
20 x 3/4 simplest form
[tex]\bf \stackrel{5}{~~\begin{matrix} 20 \\[-0.7em]\cline{1-1}\\[-5pt]\end{matrix}~~} \times \cfrac{3}{~~\begin{matrix} 4\\[-0.7em]\cline{1-1}\\[-5pt]\end{matrix}~~}\implies 5\times 3\implies 15[/tex]
The simplest form of the expression 20 x 3/4 is 15, which is achieved by first multiplying 20 by 3 to get 60, and then dividing 60 by 4.
The student has asked to find the simplest form of the mathematical expression 20 x 3/4.
To simplify this expression, you multiply 20 by 3 and then divide the result by 4.
First, calculate 20 times 3, which equals 60.
20×3 = 60
Next, divide 60 by 4, which gives you 15.
[tex]\frac{60}{4} = 15[/tex]
So, the simplest form of the expression 20 x 3/4 is 15.
Solve for g.
89 - 49 = 8
Help
The sum of two integers is 627, and the larger number is 27 more than 7 times the smaller number. Find the two integers.
Answer:
75 and 552 =627
Step-by-step explanation:
First=x
Second 7x+27
x+ 7x+27= 627
8x+27=627
8x=600
x=75
75*7+27 =525
525+27 = 552
How do you calculate 2 5/6
what is the first need to solve (2/5) x -6=-16
Answer:
x = -25
Step-by-step explanation:
Solve for x:
(2 x)/5 - 6 = -16
Hint: | Put the fractions in (2 x)/5 - 6 over a common denominator.
Put each term in (2 x)/5 - 6 over the common denominator 5: (2 x)/5 - 6 = (2 x)/5 - 30/5:
(2 x)/5 - 30/5 = -16
Hint: | Combine (2 x)/5 - 30/5 into a single fraction.
(2 x)/5 - 30/5 = (2 x - 30)/5:
(2 x - 30)/5 = -16
Hint: | Multiply both sides by a constant to simplify the equation.
Multiply both sides of (2 x - 30)/5 = -16 by 5:
(5 (2 x - 30))/5 = -16×5
Hint: | Cancel common terms in the numerator and denominator of (5 (2 x - 30))/5.
(5 (2 x - 30))/5 = 5/5×(2 x - 30) = 2 x - 30:
2 x - 30 = -16×5
Hint: | Multiply 5 and -16 together.
5 (-16) = -80:
2 x - 30 = -80
Hint: | Isolate terms with x to the left hand side.
Add 30 to both sides:
2 x + (30 - 30) = 30 - 80
Hint: | Look for the difference of two identical terms.
30 - 30 = 0:
2 x = 30 - 80
Hint: | Evaluate 30 - 80.
30 - 80 = -50:
2 x = -50
Hint: | Divide both sides by a constant to simplify the equation.
Divide both sides of 2 x = -50 by 2:
(2 x)/2 = (-50)/2
Hint: | Any nonzero number divided by itself is one.
2/2 = 1:
x = (-50)/2
Hint: | Reduce (-50)/2 to lowest terms. Start by finding the GCD of -50 and 2.
The gcd of -50 and 2 is 2, so (-50)/2 = (2 (-25))/(2×1) = 2/2×-25 = -25:
Answer: x = -25
Answer:
x = -25
Step-by-step explanation:
(2/5)x - 6= -16 (add 6 to both sides)
(2/5) x = -16 + 6
(2/5) x = -10 (multiply both sides by 5)
2x = -10 (5)
2x = -50 (divide both sides by 2)
x = -50 / 2
x = -25
Which of the following equations correctly shows the relationship between the values of x and the values of y?
Answer~ A. y=3x-4
Explanation~ Look at the X column. Start with the first row, which is 5 in the x column and 11 in the y column. Looking back at the equation. As you can see, it has the same variables that are in the table. Replace the x with the 5 from the table.
*Remember to put the 5 in parenthesis; you must always do this when plugging in numbers into your equations*
If done correctly, your equation should now look like this:
y=3(5)-4
Following PEMDAS, the order you solve order of operations, you must first multiply, as Multiplication is before Subtraction. So, you must multiply the 5 and 3. 5×3=15, so, now your equation should look like:
y=15-4
Simply subtract 4 from 15, and you should get 11. Therefore,
y=11
Continue this process down through the table to double check your work.
I hope I helped! Sorry for the dang essay lol
Draw a rectangle with six regions to expand (2x + 4) (3x2 + 5x + 7).
To expand (2x + 4) (3x^2 + 5x + 7), draw a rectangle with six regions, multiply the terms in each region and add them together. The final expanded form is 6x^3 + 22x^2 + 34x + 28.
To expand the polynomial expression (2x + 4) (3x2 + 5x + 7), we will use the rectangle (or area) method. This involves drawing a rectangle divided into six regions, each representing a product of a term from the first binomial and a term from the second trinomial.
First, draw a 2x3 rectangle, with the dimensions representing the two terms in the first binomial and the three terms in the second trinomial.
Label the length of the rectangle with the three terms from the second trinomial, 3x2, 5x, and 7.
Label the width of the rectangle with the two terms from the first binomial, 2x and 4.
Fill in each of the six regions by multiplying the term at the end of the row by the term at the top of the column. For example, the top-left region would be 2x multiplied by 3x2, giving 6x3.
Continue filling in the other five regions: 2x times 5x is 10x2, 2x times 7 is 14x, 4 times 3x2 is 12x2, 4 times 5x is 20x, and 4 times 7 is 28.
Combine like terms to get the final expanded form: 6x3 + 22x2 + 34x + 28.
Need help now please
Answer:
all work is shown and pictured
Solve for d.
|-2d| = 18
Write your answers as integers or as proper or improper fractions in simplest form.
d= or d =
Answer:
d= -9 d=9
Step-by-step explanation:
-2d = 18 -2d=-18
divide by -2
d= -9 d=9
Answer:
d=(18-1)/-2l
Step-by-step explanation:
i-2dl=18
-l
-2dl=18-l
/-2l
d=(18-1)/-2l
30 POINTS + BRAINLIEST! Please if you can, help! I'm on a timer!
Triangle PQR is transformed to triangle P'Q'R'. Triangle PQR has vertices P(4, 0), Q(0, −4), and R(−8, −4). Triangle P'Q'R' has vertices P'(1, 0), Q'(0, −1), and R'(−2, −1).
Plot triangles PQR and P'Q'R' on your own coordinate grid.
Part A: What is the scale factor of the dilation that transforms triangle PQR to triangle P'Q'R'? Explain your answer. (4 points)
Part B: Write the coordinates of triangle P"Q"R" obtained after P'Q'R' is reflected about the y-axis. (4 points)
Part C: Are the two triangles PQR and P''Q''R'' congruent? Explain your answer. (2 points)
(There is no image provided.)
See the attached picture for the answers:
Final answer:
The scale factor of the dilation that transforms triangle PQR to triangle P'Q'R' does not exist. The coordinates for the reflected triangle P''Q''R'' are P''(-1, 0), Q''(0, -1), and R''(2, -1). Triangle PQR and triangle P''Q''R'' are not congruent.
Explanation:
To find the scale factor of the dilation that transforms triangle PQR to triangle P'Q'R', we can compare the lengths of corresponding sides in the two triangles. The distance between P(4, 0) and P'(1, 0) is 3, the distance between Q(0, -4) and Q'(0, -1) is 3, and the distance between R(-8, -4) and R'(-2, -1) is 6.
Since the lengths of corresponding sides are not equal, the triangles are not similar and there is no scale factor that transforms triangle PQR to triangle P'Q'R'.
To reflect triangle P'Q'R' about the y-axis, we simply change the sign of the x-coordinate for each vertex. The coordinates for the reflected triangle P''Q''R'' are P''(-1, 0), Q''(0, -1), and R''(2, -1).
Triangle PQR and triangle P''Q''R'' are not congruent because their corresponding sides have different lengths.
Select all answers that have a value of 22?? Help..
Let's plug in the variables one by one.
6g - 2h
plug in 5 for g and 4 for h
6(5) - 2(4)
multiply
30 - 8
subtract
→ 22
20g
plug in 2 for g
20(2)
multiply
40
2(g + 1)
plug in 10 for g
2(10 + 1)
add
2(11)
multiply
→ 22
4g + 5h
plug in 1 for g and 4 for h
4(1) + 5(4)
multiply
4 + 20
add
24
Therefore, the answers that have a value of 22 are 6g - 2h and 2(g + 1)
Answer: 6g-2h when g=5 and h=4
and 2(g+1) when g=10 .
Step-by-step explanation:
1) 6g-2h
when g=5 and h=4, then we have
6(5)-2(4)=30-8=22
2) 20 g when g=2, we have
20(2)=40 ≠22
3) 2(g+1) when g=10 , we have
2(10+1)=2(11)=22
4) 4g+5h when g=1 and h=4, we have
4(1)+5(4)=4+20=21≠22
Hence, the required answer is : 6g-2h when g=5 and h=4
and 2(g+1) when g=10 .
Slope 1,passes through (2,5)
Write equation in slope intercept form
Answer:
all work is pictured and shown
Final answer:
The equation of a line with a slope of 1 that passes through the point (2,5) in slope-intercept form is y = x + 3.
Explanation:
To write the equation of a line in slope-intercept form (y = mx + b), you need to know the slope (m) and the y-intercept (b). Since the slope is given as 1 and the line passes through the point (2,5), we can use the point-slope formula to find the y-intercept.
The point-slope formula is y - y1 = m(x - x1), where m is the slope and (x1, y1) is the point the line passes through. Plugging in the values we have:
y - 5 = 1(x - 2) → y - 5 = x - 2 → y = x + 3
So, the equation of the line in slope-intercept form is y = x + 3.
3. A line goes through the points (3,4) and (-3,6).
(a) What is the slope of the line? Show your work
(b) Write the equation of the line in point-slope form. Show your work
(c) Write the equation of the line in slope-intercept form. Show your work.
Answer:
Part a) The slope is [tex]m=-\frac{1}{3}[/tex]
Part b) The equation in point slope form is [tex]y-4=-\frac{1}{3}(x-3)[/tex]
Part c) The equation in slope-intercept form is [tex]y=-\frac{1}{3}x+5[/tex]
Step-by-step explanation:
we have the points (3,4) and (-3,6)
Part a) What is the slope of the line?
The formula to calculate the slope between two points is equal to
[tex]m=\frac{y2-y1}{x2-x1}[/tex]
substitute the given points
[tex]m=\frac{6-4}{-3-3}[/tex]
[tex]m=\frac{2}{-6}[/tex]
[tex]m=-\frac{1}{3}[/tex]
Part b) Write the equation of the line in point-slope form
[tex]y-y1=m(x-x1)[/tex]
we have
[tex]m=-\frac{1}{3}[/tex]
[tex]point\ (3,4)[/tex]
substitute
[tex]y-4=-\frac{1}{3}(x-3)[/tex] ---> equation in point slope form
Part c) Write the equation of the line in slope-intercept form
[tex]y=mx+b[/tex]
we have
[tex]y-4=-\frac{1}{3}(x-3)[/tex]
Isolate the variable y
distribute right side
[tex]y-4=-\frac{1}{3}x+1[/tex]
Adds 4 both sides
[tex]y=-\frac{1}{3}x+1+4[/tex]
[tex]y=-\frac{1}{3}x+5[/tex] ---> equation in slope intercept form
The Kaibab Trail at the Grand Canyon begins at 7,000 feet above sea level. If you descend on the trail 4,500 feet to the Colorado River and then hike up 1,375 feet to a campsite, how many feet above sea level are you?
Answer:
3875 feet above sea level
Answer:
[tex]3875[/tex] [tex]feet[/tex]
Step-by-step explanation:
We first start at 7,000 feet above sea level, we then descend 4,500 feet closer to the sea level, therefore:
[tex]7,000 - 4,500[/tex]
[tex]==> 2,500[/tex]
Then we go up 1,375 feet farther from the sea level, so:
[tex]2,500 + 1,375[/tex]
[tex]==> 3,875[/tex]
Suppose the price of a certain item increases by 3.8% a total of 5 times, and then decreases by 1.4%
a total of 2 times. By what overall percent did the price increase?
Answer:
The price was increased by 17.15%
Step-by-step explanation:
step 1
we have that
[tex]100\%+3.8\%=103.8\%=103.8/100=1.038[/tex]
Let
x -----> the price of a certain item
we know that
If a price increases by 3.8% a total of 5 times
then
The new price will be equal to multiply the original price by 5 times 1.038
so
[tex]x(1.038)(1.038)(1.038)(1.038)(1.038)=x(1.038)^5[/tex]
step 2
we have that
[tex]100\%-1.4\%=98.6\%=98.6/100=0.986[/tex]
we know that
If a price decreases by 1.4% a total of 2 times
then
The new price will be equal to multiply the actual price by 2 times 0.986
The actual price is [tex]x(1.038)^5[/tex]
so
[tex]x(1.038)^5(0.986)(0.986)=x(1.038)^5(0.986)^2=1.1715x[/tex]
[tex]1.1715-1=0.1715[/tex]
convert to percentage
[tex]0.1715*100=17.15\%[/tex]
therefore
The price was increased by 17.15%
Answer: The price increased by 17.149618%.
Step-by-step explanation:
Given that the price of a certain item increases by 3.8% = 0.038 a total of 5 times.
So every time the price was (1 + 0.038) = 1.038 times the original price.
So after 5 times the price is = [tex]1.038^5=1.205[/tex] times the original price.
Then it decreased by 1.4% twice. So the new price is = [tex]1.205\cdot\left(1-0.014\right)^{2}=1.17149618[/tex] times the original price.
So the percentage increase is = [tex]\left(1.17149618-1\right)\cdot100 \%=17.149618 \%[/tex]
Learn more: https://brainly.com/question/12049968
What’s the value (ignore the time at the top)
Answer: -39g + 9
Step-by-step explanation:
PEMDAS states that multiplication must be performed before addition & subtraction
(6g × 7) - (3²g × 9) + 3³
= 42g - 81g + 9
= -39g + 9
What is an equation of the line that passes through the point (-2,3) and is parallel to the line whose equation is y=3/2x-4?
Answer:
Step-by-step explanation:
We can model a line with slope-intercept form:
[tex]y = mx + b[/tex]
where [tex]m[/tex] is the slope and [tex]b[/tex] is the Y-intercept.
We know that the new line is parallel to the given line, so the two lines have the same slope, or [tex]m = \frac{3}{2}[/tex]:
[tex]y = \frac{3}{2}x + b[/tex]
To determine [tex]b[/tex], we just need to plug in the given point that the line passes through, [tex](-2, 3)[/tex]:
[tex]y = \frac{3}{2}x + b[/tex]
[tex](3) = \frac{3}{2}(-2) + b[/tex]
[tex]3 = -3 + b[/tex]
[tex]b = 6[/tex]
This gives us the following equation:
[tex]y = \frac{3}{2}x + 6[/tex]
The equation of the line is y = (3/2)x + 6.
What is an equation of a line?The equation of a line is given by:
y = mx + c
where m is the slope of the line and c is the y-intercept.
Example:
The slope of the line y = 2x + 3 is 2.
The slope of a line that passes through (1, 2) and (2, 3) is 1.
We have,
The equation of the line passes through the point (-2,3).
y = m(1)x + c
The equation of the line is parallel to the line whose equation is y=3/2x-4.
This means,
y = (3/2)x - 4
This is in the form of y = m(2)x + c
m(2) = (3/2)
So,
m(1) = m(2)
Now,
(-2, 3) = (x, y)
y = m(1)x + c
3 = (3/2) x (-2) + c
3 = -3 + c
c = 3 + 3
c = 6
Now,
y = m(1)x + c
y = (3/2)x + 6
Thus,
The equation of the line is y = (3/2)x + 6.
Learn more about equation of a line here:
https://brainly.com/question/23087740
#SPJ6
What is the slope of the line that passes through the points (−3,1) and (7,−14)? Write your answer in simplest form.
Answer is provided in the image attached.
Using the slope formula, the slope, in simplest form, of the line that goes through (-3, 1) and (7, -14) is: [tex]\mathbf{-\frac{3}{2}}[/tex]
Recall:
Slope of a line that passes through any two points is found using the formula: [tex]m = \frac{y_2 - y_1}{x_2 - x_1}[/tex]
Given the two points that the line passes through are: (-3, 1) and (7, -14)
Let,[tex](-3, 1) = (x_1, y_1)\\\\(7, -14) = (x_2, y_2)[/tex]
Substitute[tex]m = \frac{-14 - 1}{7 - (-3)} = \frac{-15}{10} \\\\m = -\frac{3}{2}[/tex]
Therefore, using the slope formula, the slope, in simplest form, of the line that goes through (-3, 1) and (7, -14) is: [tex]-\frac{3}{2}[/tex]
Learn more here:
https://brainly.com/question/15316550
In the diagram, GB = 2x + 3..
What is GB?
Group of answer choices
15 units
10 units
30 units
5 units
Answer:
GB is 15 units
Step-by-step explanation:
see the attached figure to better understand the problem
we know that
The Centroid is a point of triangle where all 3 medians intersect
In this problem point G is the centroid of the triangle FDE
FA, EB and DC are medians of the triangle FDE.
Remember that centroid divides the median in 2:1
FA is a is median so FG:GA=2:1.
Find the value of x
[tex]\frac{FG}{GA}=\frac{2}{1}\\\\\frac{5x}{x+9}=\frac{2}{1}\\\\5x=2x+18\\\\5x-2x=18\\\\3x=18\\\\x=6[/tex]
Find the value of GB
GB=2x+3
substitute the value of x
[tex]GB=2(6)+3=15\ units[/tex]
4 - t = 3(t-1) - 5
A 3
B 6
C no solution
D Identity
Answer:
A
Step-by-step explanation:
Given
4 - t = 3(t - 1) - 5 ← distribute and simplify right side
4 - t = 3t - 3 - 5
4 - t = 3t - 8 ( subtract 3t from both sides )
4 - 4t = - 8 ( subtract 4 from both sides )
- 4t = - 12 ( divide both sides by - 4 )
t = 3
If x = 4y + 21y and y = 14 + 5, what is 3x × 7? No need to show your work.
y = 19
x = 4(19) + 21(19) = 76 + 399 = 475
3(475) × 7
1425 × 7
9975 <--- answer.
Hope this helped!
Nate
Answer:
the answer is 39
Step-by-step explanation: